2017
DOI: 10.1039/c7ra06752f
|View full text |Cite
|
Sign up to set email alerts
|

Modeling alveolar injury using microfluidic co-cultures for monitoring bleomycin-induced epithelial/fibroblastic cross-talk disorder

Abstract: Epithelial/fibroblastic cross-talk is consider to lead to pulmonary fibrosis, but its pathogenesis remains unclear because no appropriate models allow to visualize the complex disease processes at the human lung epithelial–interstitial interface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…Lung-on-chip devices have been developed to reflect the exposure of lung to threatening factors (e.g., nanoparticles, 125 drugs, 126 air pollution 127 ) and provide an insight on natural or pathogen (virus and/or bacteria) related lung disorders, 62 leading to a burden in socioeconomic life worldwide. Although there are existing animal models, which enable one to build hypothesis on diagnosis and relevant treatments, it is reported that in many diseases, promising medications have failed in human clinical trials due to toxicity in spite of successful pre-clinical results with animal models.…”
Section: Limitations and Advantagesmentioning
confidence: 99%
“…Lung-on-chip devices have been developed to reflect the exposure of lung to threatening factors (e.g., nanoparticles, 125 drugs, 126 air pollution 127 ) and provide an insight on natural or pathogen (virus and/or bacteria) related lung disorders, 62 leading to a burden in socioeconomic life worldwide. Although there are existing animal models, which enable one to build hypothesis on diagnosis and relevant treatments, it is reported that in many diseases, promising medications have failed in human clinical trials due to toxicity in spite of successful pre-clinical results with animal models.…”
Section: Limitations and Advantagesmentioning
confidence: 99%
“…This allows for studying epithelial injury, fibroblast, and macrophage migration under fibrosis. 160 It could be concluded that altering the microenvironment and change in epithelial cross-talk would activate fibroblasts and cause the development of pathological fibroblastic foci.…”
Section: Lungs-on-a-chipmentioning
confidence: 99%
“…Pulmonary fibrosis was studied in the co-cultures of A549 alveolar epithelial cells, MRC-5 fibroblasts, and THP-1 macrophages treated with bleomycin in a microfluidic system [85] and in pulmospheres generated from pulmonary fibrosis patients [86]. The pulmospheres can, for instance, be used as a screening system for anti-fibrotic drugs.…”
Section: Cellular Models For Lung Diseasesmentioning
confidence: 99%